Sleep inertia: current insights - Hilditch CJ (Dove Medical Press, 2019)
Cassie J Hilditch,1 Andrew W McHill21Fatigue Countermeasures Laboratory, San Jose State University Research Foundation, Moffett Field, San Jose, CA 94035, USA; 2Oregon Institute of Occupational Health Sciences, Oregon Health and Science University, Portland, OR 97239, USACorrespondence: Andrew W McHillOregon Institute of Occupational Health Sciences, Oregon Health and Science University, 3181 SW Sam Jackson Park Road - L606Portland, OR 97239 USATel +1 503 494 2594Fax +1 503 494 4278Email mchill@ohsu.eduAbstract: Sleep inertia, or the grogginess felt upon awakening, is associated with significant cognitive performance decrements that dissipate as time awake increases. This impairment in cognitive performance has been observed in both tightly controlled in-laboratory studies and in real-world scenarios. Further, these decrements in performance are exaggerated by prior sleep loss and the time of day in which a person awakens. This review will examine current insights into the causes of sleep inertia, factors that may positively or negatively influence the degree of sleep inertia, the consequences of sleep inertia both in the laboratory and in real-world settings, and lastly discuss potential countermeasures to lessen the impact of sleep inertia.Keywords: cognitive performance, countermeasures, grogginess